Modelo para orquestração de redes de inovação: um estudo de caso - Toigo, Taisson (Universidade do Vale do Rio dos Sinos, 2020)
Innovation Networks make it possible to establish cooperative relations between organizations aiming at a result in terms of innovation. Orchestrated innovation networks are a recent and growing phenomenon and occur when an organization leads the entire process, from identifying an opportunity to achieving results. The orchestration of innovation networks requires an orchestrating organization - which will assume leadership through its power and prominence, without the need for hierarchy. For the orchestration to take place and to obtain the results, the orchestrating organization will need to execute processes. For that, it will be necessary to have specific skills (at the organizational level) and skills (at the individual level). Built based on the theory of Dynamic Capabilities (CD) and the literature on the orchestration of innovation networks and network capacities, this thesis aimed to propose a model for the orchestration of innovation networks covering processes, capabilities, and skills. For this, I conducted an exploratory study through a qualitative approach in a single case study with incorporated units. The empirical object was a Brazilian multinational in the cosmetic industry. Three innovation networks were investigated, constituted in the form of innovation projects. The main result is a model for the orchestration of innovation networks that contemplates the stages, the processes executed in each stage, and the specific capacities and skills to perform these processes. The model includes three stages, which start in the search and identification of opportunities for an orchestrated innovation network, going through the design and formation of the network until the stage where the orchestration occurs before the results. The thesis brings theoretical propositions for future validation and theoretical and managerial contributions, as well as suggestions for future studies.
Keywords: Orquestração de redes de inovação; Capacidades de network; Inovação; Redes; Orchestration of innovation networks; Network capabilities; Innovation; Networks; ACCNPQ::Ciências Sociais Aplicadas::Administração